Observation of resistive Weibel instability in intense laser plasma. (29th June 2020) - Krishnamurthy, S.; Makur, K.; Ramakrishna, B.
Abstract: We observe experimentally periodic proton beam filamentation in laser-produced dense plasma using multilayered (CH–Al–CH) sandwich targets. The accelerated MeV proton beams from these targets exhibit periodic frozen filaments up to 5–10 µm as a result of resistive Weibel instabilities in the expanding plasma. The evolution of strong self-generated resistive magnetic fields at the targets interface is attributed to such plasma effects, which are supported, by our theory and simulations. We suggest that the resistive Weibel instability could be effectively employed to understand the evolution of magnetic fields in laser-generated plasma in the astrophysics scenario or the advanced fast igniter approach of the inertial confinement fusion.